FAKTOR DETERMINAN KEBERHASILAN PRAKTEK KEWIRAUSAHAAN MAHASISWA - Hadiyati, Hadiyati; Fatkhurahman, Fatkhurahman; Aznuriyandi, Aznuriyandi (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2024)
Entrepreneurship practices allow students to learn relevant skills, such as problem solving, creativity, leadership, decision making, and risk management. These skills are not only useful in entrepreneurship but also in any career. By participating in entrepreneurship practices, students learn to think innovatively and dare to take calculated risks. This helps them to be more proactive in seeking opportunities and solutions, both in the business world and in other fields of work. However, it is still necessary to study the success of students in entrepreneurship practices. The output achieved is the identification of factors that influence the success of students in carrying out entrepreneurship practices. The methodology in this study uses a quantitative approach, the respondents in this study were students who were carrying out entrepreneurship practices. Data were collected using questionnaires and interviews and analyzed using multiple linear regression analysis tools using the smarPLS4 application. The results of the study prove that of the ten factors suspected of influencing the success of student business practices, four significant variables are known, namely creativity and innovation factors, self-motivation, work culture and networks. While the other six factors such as: entrepreneurial support and guidance factors, interest, financial literacy, utilization of technology, practical entrepreneurial experience and family support do not have a significant effect on the success of student entrepreneurship practices.